Character Education in The Online Defense Process: Study Analysis of Morals Aqidah Learning - M Wafiyul Ahdi; Mokhammad Farkhannudin (SCHOOLAR: Social and Literature Study in Education, 2022)
Character Education is upahaya to realize the generation of the nation that is smart and good or has noble morals and personality of Indonesia. The success of character education hints at learning is not necessarily seen from the perspective of the cognitive realm alone through how the balance of the cognitive, affective and psychomotor realms whose estuary is to realize the whole human being becomes more moral, in this condition the covid 19 pandemic is currently a challenge for the world of education especially in character education such as in public schools in MAUWH Tambakberas Jombang the implementation of educators is conducted online first da lam character education process in the learning of Morals Aqidah that prioritizes smoothness in the online learning process, to get maximum results.in instilling good character values.